1967
DOI: 10.1177/000348946707600511
|View full text |Cite
|
Sign up to set email alerts
|

LXXXIV Reparative Granuloma following Stapedectomy: A Clinical Entity

Abstract: The formation of reparative granuloma as one of the causes for sensorineural hearing loss as a complication of stapedectomy has been reported previously.6,13,17 The purpose of this paper is to present our experiences with this problem and to show that this condition can be diagnosed and treated with good results in many cases.The incidence of sensorineural loss from all causes following stapedectomy was reported in several studies 8 ,9 ,l1 to range from 0.6 per cent to 3 per cent. Harris and Weiss, on the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Accidental foreign bodies including cotton wool fibers, linen fibers from drapes, glove powder (talc or starch) [10] and fractured Teflon fragments have been considered to stimulate foreign body granuloma. However, Kaufman et al [6] and Buntner et al [5] found these materials to be non-contributory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accidental foreign bodies including cotton wool fibers, linen fibers from drapes, glove powder (talc or starch) [10] and fractured Teflon fragments have been considered to stimulate foreign body granuloma. However, Kaufman et al [6] and Buntner et al [5] found these materials to be non-contributory.…”
Section: Discussionmentioning
confidence: 99%
“…Presenting symptoms usually surface one to eight weeks following surgery and most commonly involve vertigo but may include sensorineural hearing loss, progressive mixed hearing loss, sudden hearing loss and tinnitus [3] [6]. Our patient presented with progressive mixed hearing loss, vertigo and otalgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(E) Hydroxyapetite bone cement can also be used to rebuild the shortened incus long process onto which the prosthesis can be secured but since they were taken off the market, this is an even rarer occurrence. Some are thought to be due to powder on gloves, but this has not been proven [29]. A recent report involved a granuloma after acellular porcine small intestinal submucosa was used to seal the piston at the oval window (Fig.…”
Section: Reparative Granulomamentioning
confidence: 99%
“…This is a rare condition that occurs usually 7–15th-day post-operatively after a stapedectomy [ 29 ]. It was highly associated in the past with manufactured gelfoam-wire prostheses, but since they were taken off the market, this is an even rarer occurrence.…”
Section: Introductionmentioning
confidence: 99%